2018
DOI: 10.3389/fnhum.2018.00426
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging Detects Microstructural Differences of Visual Pathway in Patients With Primary Open-Angle Glaucoma and Ocular Hypertension

Abstract: Ocular hypertension (OHT), the common situation in adult patients in the outpatients, occurs ∼5% worldwide. However, there are still some practical problems in differentiation of OHT with early primary open-angle glaucoma (POAG) using current standard methods. Application of high resolution diffusion tensor imaging (DTI) enables us to the differentiate axonal architecture of visual pathway between POAG and OHT subjects. Among 32 POAG patients recruited (15 OHT and 14 control subjects), 62.5% of glaucoma were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Primary open-angle glaucoma is the most common type of glaucoma ( Yuan et al, 2013 ). The early clinical manifestations are almost insidious, and visual function may be irreversibly damaged at onset ( Song et al, 2018 ). Therefore, proactively identifying the risk factors for POAG has become the central point of POAG prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Primary open-angle glaucoma is the most common type of glaucoma ( Yuan et al, 2013 ). The early clinical manifestations are almost insidious, and visual function may be irreversibly damaged at onset ( Song et al, 2018 ). Therefore, proactively identifying the risk factors for POAG has become the central point of POAG prevention.…”
Section: Discussionmentioning
confidence: 99%
“…They are sensitive to high-frequency space and transmit red and green color information (Schiller and Malpeli, 1978 ; Hendry and Calkins, 1998 ; Masri et al, 2020 ). Several studies have shown that both the M and P layers of the LGN are damaged in monkey glaucoma models (Dandona et al, 1991 ; Chaturvedi et al, 1993 ; Vickers et al, 1997 ; Weber et al, 2000 ; Yucel et al, 2000 , 2001 ; Sasaoka et al, 2008 ; Ito et al, 2009 , 2011 ; Yan et al, 2017 ), and this conclusion has also been confirmed in human glaucoma patients (Gupta et al, 2006 , 2009 ; Dai et al, 2011 ; Hernowo et al, 2011 ; Shimazawa et al, 2012 ; Chen et al, 2013b ; Lee et al, 2014 ; Wang et al, 2015 , 2016 ; Zhang et al, 2016 ; Ersoz et al, 2017 ; Song et al, 2018 ; Xu et al, 2018 ; Li et al, 2019a ; Kosior-Jarecka et al, 2020 ). Weber et al used a laser-induced chronic glaucoma monkey model to explore changes in size, density, and number of LGN neurons during glaucoma.…”
Section: Transneuronal Degeneration In Glaucoma Brainmentioning
confidence: 72%
“…Recently, diffusion tensor imaging (DTI) has enabled researchers to investigate tissue abnormalities of visual white matter tracts, such as the optic tract (OT) and optic radiation (OR; Figure 1B), in living humans 4,5 . DTI studies have demonstrated that glaucoma patients show abnormalities in diffusivity measurements, such as fractional anisotropy (FA) 6 , along these tracts [7][8][9][10][11][12][13][14][15][16][17][18] . However, a major limitation is that DTI-based metrics do not directly correlate with specific types of tissue properties, such as axon diameter and myelination 5,[19][20][21][22][23] .…”
Section: Precismentioning
confidence: 99%